2003
DOI: 10.1152/jn.00449.2003
|View full text |Cite
|
Sign up to set email alerts
|

Axotomy-Induced Expression of Calcium-Activated Chloride Current in Subpopulations of Mouse Dorsal Root Ganglion Neurons

Abstract: and Frédérique Scamps. Axotomy-induced expression of calciumactivated chloride current in subpopulations of mouse dorsal root ganglion neurons. J Neurophysiol 90: 3764 -3773, 2003. First published August 27, 2003 10.1152/jn.00449.2003. Whole cell patchclamp recordings of calcium-activated chloride current [I Cl(Ca) ] were made from adult sensory neurons of naive and axotomized mouse L 4 -L 6 lumbar dorsal root ganglia after 1 day of culture in vitro. A basal I Cl(Ca) was specifically expressed in a subset of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
92
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 83 publications
(104 citation statements)
references
References 49 publications
10
92
0
2
Order By: Relevance
“…DRGs. This time-point corresponds with the increased expression of ICl(Ca) in axotomized DRG neurons [1] . The results, shown in Fig.…”
Section: Tweety Family Expression In Adult Drgmentioning
confidence: 76%
See 1 more Smart Citation
“…DRGs. This time-point corresponds with the increased expression of ICl(Ca) in axotomized DRG neurons [1] . The results, shown in Fig.…”
Section: Tweety Family Expression In Adult Drgmentioning
confidence: 76%
“…These neurons express many types of ion channels, some of which have been shown to be responsible for the specific functional properties of particular neuronal sub-types responsible for defined sensory modalities. We recently reported the induction of a calcium-activated chloride current (I Cl(Ca) ) in a discrete population of sensory neurons of the dorsal root ganglion [1] . Axotomy of the sciatic nerve led to the massive induction of I Cl(Ca) in the vast majority of neurons of medium and large cell body diameter, generally thought to be low-threshold skin and muscle innervating neurons conveying touch and proprioceptive information.…”
Section: Introductionmentioning
confidence: 99%
“…Sensory neurons display robust CaCC currents (Mayer, 1985; Ward & Kenyon, 2000; Andre et al . 2003), which are most likely mediated by ANO1 channels (Liu et al . 2010; Cho et al .…”
Section: Coupling Between Ano1 and Endoplasmic Reticulum; Is This A Gmentioning
confidence: 99%
“…However, subdivision of neurons into large (mostly mechano‐sensitive), medium and small (mostly nociceptive) neurons later revealed that while medium and large neurons express VGCC‐coupled CaCCs (Andre et al . 2003; Boudes et al . 2009; Boudes & Scamps, 2012), in small neurons such coupling is rarely seen (Andre et al .…”
Section: Coupling Between Ano1 and Endoplasmic Reticulum; Is This A Gmentioning
confidence: 99%
See 1 more Smart Citation